The influence of thermal conditions on perfection in GaₓIn₁-ₓSb single crystals - Kushnarev, A.V.; Kozhemyakin, G.N. (Functional Materials, 2005)
The influence of the temperature gradient on the appearance of macro-cracks in growing GaₓIn₁-ₓSb single crystals by Czocralski method is shown. The decrease of axial temperature gradient dT/dz to 15 K/cm and radial dT/dx to 5 K/cm has allowed obtaining the single crystals without the cracks. The thermal field in Ga₀.₀₃In₀.₉₇Sb single crystal grown with use of experimental values of the temperature gradients is calculated.